ANALISIS EKONOMI PENGEMBANGAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO: STUDI KASUS DI KABUPATEN MUARA ENIM, SUMATERA SELATAN - Nur Arifatul Ulya; Efendi Agus Waluyo; Adi Kunarso (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
Micro Hydro Powerplant (MHP) is one form of water utilization in upper Musi watershed to generate electricity. This paper aims to analyse the feasibility of the development and management of self-help MHP to support forest resource conservations. Financial and economic analysis are applied to determine the feasibility of the development and management of the self-help MHP. The result indicates that the construction and management of the self-help MHP in the research area are not feasible, so that they do not guarantee the sustainability of the MHP in the long term period. Development and management of MHP will be financially feasible when it uses postpaid electricity tariff scheme of State Electricity Company (SEC) for power limit up to 450 VA, and economically feasible if it uses postpaid electricity tariff scheme for power limit (SEC) up to 1,300 VA. It is necessary to increase the capacity of the community both technical and economic aspects in the management of MHP for the sustainability of electricity supply from the MHP. Water utilization for the MHP increases the collective awareness to conserve forest resources.